Stronger Association of Common Variants in TCF7L2 Gene with Nonobese Type 2 Diabetes in the Latvian Population - Kalnina, I.; Geldnere, K.; Tarasova, L.; Nikitina-Zake, L.; Peculis, R.; Fridmanis, D.; Pirags, V.; Klovins, J. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Polymorphisms in the gene coding for transcription factor 7 like 2 (TCF7L2) are recognized as the strongest common genetic risk factors for type 2 diabetes (T2D) across multiple ethnicities. This study was conducted to evaluate an association between TCF7L2 variants and diabetes susceptibility in the population of Latvia. We genotyped 4 single nucleotide polymorphisms (SNP) rs7901695, rs7903146, rs11196205 and rs12255372 in 1 093 controls and 1 043 diabetic subjects. Association with T2D was found for 3 SNPs rs7901695, rs7903146 and rs12255372 in the whole sample (under an additive genetic model, the adjusted odds ratios (OR) were 1.26, 95% CI [1.08–1.48], P=0.003; OR=1.32, 95% CI [1.12–1.55], P=0.001 and OR=1.35, 95% CI [1.15–1.60], P=0.0004 respectively). In addition observed effects on T2D susceptibility for analysed SNPs were higher among subjects with BMI under 30 kg/m2. The impact of TCF7L2 variation on T2D risk in Latvian population is compatible with that demonstrated by a range of studies conducted in various ethnic groups.
Keywords: association study; polymorphism; T2D